Identification of priority areas for conservation in Argentina: quantitative biogeography insights from mygalomorph spiders (Araneae: Mygalomorphae) - Ferretti, Nelson Edgardo (2014)
Conservation biogeography involves the application of biogeographical principles and methods to conservation issues. The identification of areas of endemism is important for both historical biogeography and conservation. Mygalomorphs spiders have poor vagility, limited dispersal mechanisms and sedentary habits. In this study we use a panbiogeographical approach (through track analysis) and the optimality criterion (NDM) to analyze the distributional patterns in order to identify areas of endemism and to prioritize areas for conservation in Argentina. We identified seven generalized tracks and four biogeographical nodes. The analysis of the 2° matrix examined by NDM allowed the identification of eight areas of endemism; from the analysis of the 1.5° matrix, NDM resulted in three areas of endemism; and the analysis of the 1° and 0.5° matrices identified one area of endemism each. The more relevant areas identified in this study were located at the Atlantic Forest, Pampa, Monte and Chaco. Other identified areas were Yungas and the hilly systems of Ventania and Tandilia (southern Pampa). We suggest that these results can indicate where to prioritize investment in creating new protected areas, in order to preserve the processes that generate the biogeographic patterns exhibited by this biota.